Edukasi Pasien Dan Keluarga Terkait Keselamatan Pasien Di Rumah Sakit Umum Mitra Sejati Tahun 2024 - Diah Karlina (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2025)
Patient safety is a global issue. The losses caused by neglecting patient safety are substantial. Many patients experience unintended harmful events during care at healthcare facilities. Nurses, as one of the frontline professions, are responsible for patient safety. Therefore, it is necessary to address this issue, one of which is through education. The purpose of this community service is to provide education on patient safety within the hospital environment, for both patients and their families. The methods used include lectures, discussions, and evaluations. The results obtained after the education were that all participants understood patient safety within the hospital environment. It is recommended that this education be conducted consistently, so it can reduce adverse events for patients and families.